Jornalismo, humor e política: a cobertura das eleições presidenciais de 2010 pelo CQC e sua contribuição para o debate político - Ramos, Daniela Atalla da Silva (2013)
My interest for COC first as televiewer and, later, as a researcher, was motivated by the apparently innovative combination between journalism and humor in which the TV show is based. Having as goal to perform an analysis of this TV show under the perspective of political communication and sociology, I have looked in the first Chapter of this work to describe what is COC, which is the audience profile and, having as theoretical framework the teachings of authors such as Bourdieu, Azevedo e Porto, raise some questions about mass communication, what is news and what is the criteria used by journalism to define a journalistic agenda. In the second chapter, 1 tried to bring a history of political humor in Brazil, with the purpose of inserting COC in such historic background; as well as to aggregate the contributions of the "Semantic Mechanisms of Humor" (of Raskin) and of "Dialogic Analysis of Discourse" (of Bakhtin), to begin setting up the construction of an overview of the combination among humor, politics and journalism. In the third chapter, 1 have made an analysis of the journalistic coverage performed by COC of Presidential Elections of 2010, bringing examples on the way the TV show has addressed the agenda of TV Electoral Propaganda, the profiles and proposals of the candidates. Later, 1 have reached the conclusion that the combination of humor, politics and journalism effectively results in little information to the voter - and in the reinforcement of some stereotypes